A Study on Assessment of Adverse Drug Reactions in Patients with Tuberculosis in a Tertiary Care Teaching Hospital - Javedh Shareef, U. P. Nandakumar, Mahalingeshwara Bhat (Journal of Applied Pharmaceutical Science, 2018)
Tuberculosis is a chronic infectious disease caused by mycobacterium tuberculosis leading to increased morbidity and mortality. Adverse drug reactions associated with Anti-tubercular drugs can result in non-compliance and therapeutic failure. The present study was aimed to identify the adverse drug reactions caused by anti-tubercular drugs and their assessment by using causality, severity and preventability scales. All the patients with tuberculosis admitted during the study period who met the study criteria were included and monitored for adverse drug reactions and were then subjected to assessment of causality, severity and preventability. A total of 95 patients were followed during the study period, out of which 22 patients developed 33 adverse drug reactions. Higher incidence of adverse drug reactions was observed in females (54.5%) than males (45.4%). The most common system associated with adverse drug reactions was found to be gastrointestinal system (45.5%). On evaluation of the causality assessment of adverse drugs reactions, majority of them were found to be ‘probable’ by both WHO and Naranjo scales. The severity assessment of adverse drug reactions by using Hart wig et al. showed that 60.7% of the adverse drug reactions were ‘moderate’ and 36.4% were ‘mild’. Preventability assessment showed that majority of the adverse drug reactions was ‘probably preventable’. The present study shows that implementing a system for regular adverse drug reactions monitoring may help to minimize morbidity and improve patient compliance and achieve better therapeutic outcome.
Keywords: Tuberculosis, Adverse drug reactions, Causality assess¬ment, Severity assessment.